Interaction on impression of place at historic waterfront - Mohd Yunus, Mohd Yazid; Nangkula, Utaberta; Ismail, Nor Atiah; Mohd. Ariffin, Noor Fazamimah; Ismail, Sumarni; Hussain, Mohd Amirul (American-Eurasian Network for Scientific Information, 2015)
Background: Impression of place is a key concept for a good historic waterfront development, which use it as a measure of nostalgia integrity in a waterfront area. Urban designer and master planner use the same term to promote human perceptual to historic world. Adopting a case study at historic waterfront, these paper purposes to discover the interaction on impression of place at historic waterfront. This paper review on literature on how the interplay of impression of place has an impact on emotional response as one observes and experiences the historic waterfront. This evaluation will analyzed and study on literature review from journal, books and other resources about the function of impression of place at historic waterfront. As a result this paper wills use as references to other need in role enhance the visual quality at historic waterfront that influenced from impression of place.